2011
DOI: 10.1097/mao.0b013e31822e938d
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Diffusion-Weighted Magnetic Resonance Imaging in the Assessment of Postoperative Cholesteatoma

Abstract: The available evidence suggests that non-EPI such as half-Fourier acquisition single-shot turbo spin echo sequences are more reliable in identifying residual or recurrent cholesteatoma. This is a promising radiologic investigation; however, we think further studies are required with more patients and long-term results to establish its place as an alternative to a second-stage surgery after canal wall up surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 34 publications
5
82
2
1
Order By: Relevance
“…These results are similar to previously published qualitative studies in the literature reporting 100% sensitivity and specificity (22)(23)(24)(25). However, most qualitative non-echoplanar DWI studies in the literature have reported slightly lower sensitivity (82%-92%) and specificity (86%-96%) values (5,6,14,19,(26)(27)(28). The false-negative cases and thus the relatively lower sensitivity levels for the non-echoplanar evaluation of CS are reported to be due to the insufficiency of the technique to demonstrate mural and very small lesions (17,19,22).…”
Section: Discussionsupporting
confidence: 79%
“…These results are similar to previously published qualitative studies in the literature reporting 100% sensitivity and specificity (22)(23)(24)(25). However, most qualitative non-echoplanar DWI studies in the literature have reported slightly lower sensitivity (82%-92%) and specificity (86%-96%) values (5,6,14,19,(26)(27)(28). The false-negative cases and thus the relatively lower sensitivity levels for the non-echoplanar evaluation of CS are reported to be due to the insufficiency of the technique to demonstrate mural and very small lesions (17,19,22).…”
Section: Discussionsupporting
confidence: 79%
“…Use of this imaging modality may help prevent unnecessary surgery for patients when there is concern for residual or recurrent cholesteatoma. 5 Recently, many have favored a tailored approach, with a second look reserved for those patients when cholesteatoma was thought to be left behind at the primary surgery.. The studies presented here show that a selective approach to staging cholesteatoma surgery, in both adults and pediatric patients, is effective and appropriate and will reduce unnecessary procedures.…”
Section: Discussionmentioning
confidence: 71%
“…5 Jindal et al performed a systematic review of diffusion-weighted imaging, evaluating both echo planar imaging (EPI) and nonecho planar imaging (non-EPI) techniques. 5 Sixteen studies were included with a total of 432 patients. Echo planar imaging had a sensitivity of 70.6%, specificity of 87.3%, positive predictive value (PPV) of 91.4%, and negative predictive value (NPV) of 74.1%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SS EPI-DWI frequently leads to artifacts, which could mask areas of restricted diffusion in a cholesteatoma and therefore SS EPI-DWI is no longer recommended [60,61]. The presently used non-EPI DWI method combines a sensitivity of 91.4 % and a positive predictive value of 97.3 % with a negative predictive value of 85 % [62]. Non-EPI DWI thus can prevent unnecessary revision surgery in patients who are suspected of having recurrent or residual disease as CT cannot discriminate cholesteatoma within a soft-tissue mass or partially filled with nonspecific imaging abnormalities [62].…”
Section: Diffusion-weighted Imaging (Epi-dwi Non-epi-dwi Resolve)mentioning
confidence: 99%
“…The presently used non-EPI DWI method combines a sensitivity of 91.4 % and a positive predictive value of 97.3 % with a negative predictive value of 85 % [62]. Non-EPI DWI thus can prevent unnecessary revision surgery in patients who are suspected of having recurrent or residual disease as CT cannot discriminate cholesteatoma within a soft-tissue mass or partially filled with nonspecific imaging abnormalities [62]. DWI may also replace delayed gadolinium-enhanced T1w sequences [60].…”
Section: Diffusion-weighted Imaging (Epi-dwi Non-epi-dwi Resolve)mentioning
confidence: 99%